Evaluation of response to first-line treatment for chronic myeloid leukemia: has imatinib been outperformed?. (April 2014) - Lau, Anna; Heaney, Mark L
SUMMARY : Achievement of deep, early response to first-line tyrosine kinase inhibitor (TKI) therapy significantly predicts favorable long-term outcome in chronic myeloid leukemia (CML). Although imatinib is an effective first-line treatment, nilotinib and dasatinib, more potent TKIs, are more effective in eliciting deep, rapid response to therapy and preventing disease progression, and may represent superior first-line treatment options in CML. Although many patients who are resistant to, or intolerant of first-line imatinib can be rescued by second-line TKIs, the clinical outlook for these patients is inferior, particularly if there is disease progression. Therefore, clinicians should strive to minimize the occurrence of disease progression, and optimize the depth of response early in the treatment course in patients with chronic-phase CML.